Menciptakan Kepercayaan dan Kejujuran Pasangan Suami Istri di Era Media Sosial - Inka Salsabila (Assertive: Islamic Counseling Journal, 2025)
The development of technology and the increasing use of social media have influenced the dynamics of interpersonal relationships, including in marriage. This phenomenon presents new challenges related to transparency and potential conflicts arising from the use of social media. The purpose of this research is to understand how to foster trust and honesty in the relationship between spouses in the digital age, commonly referred to as the Social Media Era. The method employed is a qualitative approach, involving in-depth interviews with several married couples. The research results were then analyzed to identify the findings related to the research focus. The results of the study show that social media can be a tool that supports communication and openness in creating trust and honesty for married couples, but also has the potential to trigger suspicion and conflict due to a lack of understanding of digital dynamics. Couples must have awareness and skills to interact healthily on digital platforms, which can help maintain the harmony of husband-and-wife relationships. These findings highlight the importance of understanding and healthy interaction skills on digital platforms in maintaining harmonious relationships. This research provides valuable insights for couples to manage trust and honesty in the era of social media, while also highlighting the need for education about the impact of technology on marital relationships.   Perkembangan teknologi dan meningkatnya penggunaan media sosial telah memengaruhi dinamika hubungan interpersonal, termasuk dalam pernikahan. Fenomena ini menimbulkan tantangan baru terkait transparansi dan potensi konflik akibat penggunaan media sosial. Tujuan penelitian ini adalah memahami cara menciptakan kepercayaan dan kejujuran dalam hubungan antara suami dan istri di Era Media Sosial. Metode yang digunakan adalah pendekatan kualitatif dengan wawancara mendalam terhadap sejumlah pasangan suami istri. Data hasil penelitian kemudian dianalisis untuk mengidentifikasi hasil penelitian yang berkaitan dengan fokus penelitian. Hasil penelitian menunjukkan bahwa media sosial dapat menjadi alat yang mendukung komunikasi dan keterbukaan dalam menciptakan kepercayaan dan kejujuran bagi pasangan suami istri, namun juga berpotensi memicu kecurigaan dan konflik akibat kurangnya pemahaman terhadap dinamika digital. Pasangan harus memiliki kesadaran dan keterampilan berinteraksi secara sehat di platform digital cenderung menjaga keharmonisan hubungan suami istri. Temuan ini menekankan pentingnya kesadaran dan keterampilan berinteraksi secara sehat di platform digital agar hubungan tetap harmonis. Penelitian ini memberikan wawasan bagi pasangan untuk mengelola kepercayaan dan kejujuran di era media sosial, serta mendorong perlunya edukasi tentang dampak teknologi terhadap hubungan pernikahan.